A New social cognitive developmental perspective on prejudice the interplay between morality and group identity - Rutland,Adam; Killen, Melanie; Abrams, Dominic (Sage Publications, 2010)
We argue that prejudice should be investigated in the context of social-cognitive development and the interplay between morality and group identity. Our new perspective examines how children consider group identity (and group norms) along with their developing moral beliefs about fairness and justice. This is achieved by developing an integrated framework drawing on developmental and social psychological theories of prejudice. This synthesis results in a perspective that provides a more contextualized analysis of prejudice development than that previously offered by developmental theories. We describe research that supports our view that social norms, intergroup contact, and perceived outgroup threat affect the relative weight children place on moral and group-based criteria during the development of prejudice.